Reflection of Indian Manners and Customs in The Writings of RK Narayan - Kaur, Amandeep; Singh, Mr. Kuldeep (International Journal of Psychosocial Rehabilitation, 2020)
This paper investigates how the works of R.K. Narayan helps in getting the subtleties of Indian Culture and its struggles for certain models from his works. Narayan’s scholarly manifestations are vivid textures woven with the unpredictable strings of Indian culture like practices, customs, strict convictions, beliefs, harsh and sweet tunes of adoration and marriage, struggle among Indian and unfamiliar cultures, hole between ages, and so forth, yet with the bit of humor. The culture and life of a country can be described in a foreign language. Here, a country like India, its culture, the way people live here and their mind-set can be explained in a foreign language like English, but there is always an emotion missing which cannot be shown in any foreign language, still R.K. Narayan with his art of narration has done this with a touch of languages like, Hindi, Urdu and Sanskrit. This paper uncovers the Indian lifestyle and furthermore the culture and custom of India. R.K. Narayan has utilized run of the mill Indian characters and Indian air to depict Indian culture.